A review of droplet resonators: Operation method and application. (December 2016) - Wang, Yan; Li, Hanyang; Zhao, Liyuan; Wu, Bing; Liu, Shuangqiang; Liu, Yongjun; Yang, Jun
Abstract: Droplet resonators hold promise as a special class of optical cavities for numerous applications in micro-optical. Owing to liquid surface tension, droplet resonators possess nearly perfect spherical geometry and exceptionally smooth surfaces that prompt more and more meritorious applications to be exploit. Herein, we survey two typical operation methods of the droplet resonators, passive and active droplet resonator. Besides, droplet applications as high-performance lasers and sensors have been discussed. Although these applications have brought us tremendous value, the research for droplet resonators are still in its infancy, added potential application and intrinsic investigation of the droplet resonators should be developed in the future work. Highlights: The droplet resonators have aroused our interesting in recent years. The operation methods of the droplet resonators are reviewed. The droplet applications as high-performance lasers and sensors are introduced. Challenges for promoting the studies of droplet resonators are discussed.